2022
DOI: 10.1186/s12883-022-02687-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of disease progression and genetic correlation in ambulatory Iranian boys with Duchenne muscular dystrophy

Abstract: Background Duchenne muscular dystrophy (DMD) is the most common muscular dystrophy in the pediatric population. The manifestations of this disease include progressive muscle weakness, gait dysfunction, and motor impairment, leading to a loss of ambulation by the age of 13 years. Molecular diagnosis is the standard diagnostic tool for DMD. This study aimed to investigate disease progression and genetic patterns in Iranian ambulant boys and to find the correlation between genotypes and motor func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Furthermore, the survival analysis for the follow-up evaluation of the patients revealed that, with the progression of the disease, the patients in Group 1 were more prone to becoming wheelchairbound at a younger age compared to those in Group 2 (p = 0.004), as depicted in Table 3 and Figure 4. The reported data on the age of wheelchair dependency in DMD patients of different populations are as follows: in India, the age is 10.4 years [18] and 13 years [34]; in Iran, the age is 10.9 years [35]; in Saudi Arabia, the age is 10.1 years [36]; in the Netherlands, the age is 9.7 years [37]; and in the UK, according to the North Star database and other related studies, the age is 13 years [10,38]. The variability observed in the age at which individuals become dependent on wheelchairs in different populations can potentially be attributed to regional disparities in patient management, healthcare resources, the socioeconomic background of the patients, genetic factors, and the influence of disease modifier genes specific to certain populations [30,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the survival analysis for the follow-up evaluation of the patients revealed that, with the progression of the disease, the patients in Group 1 were more prone to becoming wheelchairbound at a younger age compared to those in Group 2 (p = 0.004), as depicted in Table 3 and Figure 4. The reported data on the age of wheelchair dependency in DMD patients of different populations are as follows: in India, the age is 10.4 years [18] and 13 years [34]; in Iran, the age is 10.9 years [35]; in Saudi Arabia, the age is 10.1 years [36]; in the Netherlands, the age is 9.7 years [37]; and in the UK, according to the North Star database and other related studies, the age is 13 years [10,38]. The variability observed in the age at which individuals become dependent on wheelchairs in different populations can potentially be attributed to regional disparities in patient management, healthcare resources, the socioeconomic background of the patients, genetic factors, and the influence of disease modifier genes specific to certain populations [30,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…En nuestro estudio, la edad promedio en el momento de evaluación molecular fue 6,5 años en pacientes con DMD/ DMB. Esta cifra es relativamente superior a estudios realizados en Italia, Irán y Noruega que han informado edades promedios de 3,90, 4,00 y 5,05 años, respectivamente (18)(19)(20). Además, un estudio peruano realizado en cuatro establecimientos de referencia nacional entre el 2015 al 2018 reportaron una edad promedio de 9,8 años para la evaluación molecular.…”
Section: Discussionunclassified
“…As of 31 May 2022, more than 7100 DMD mutations, including exon deletions, exon duplications, and point mutations, have been described in the Leiden Open Variation Database (LOVD) and the UMD-DMD France Database. Exon duplication is the most common mutation, accounting for approximately 7% of all DMD pathogenic mutations [ 7 , 8 ]. Approximately 1 in 5224 fetuses carry maternally inherited exon duplications of the DMD gene [ 9 ].…”
Section: Introductionmentioning
confidence: 99%